Candida Infections and Therapeutic Strategies: Mechanisms of Action for Traditional and Alternative Agents - de Oliveira Santos, Giselle C.; Vasconcelos, Cleydlenne C.; Lopes, Alberto J. O.; de Sousa Cartágenes, Maria do S.; Filho, Allan K. D. B.; do Nascimento, Flávia R. F.; Ramos, Ricardo M.; Pires, Emygdia R. R. B.; de Andrade, Marcelo S.; Rocha, Flaviane M. G.; de Andrade Monteiro, Cristina (Frontiers in Microbiology, 2018)
The Candida genus comprises opportunistic fungi that can become pathogenic when the immune system of the host fails. Candida albicans is the most important and prevalent species. Polyenes, fluoropyrimidines, echinocandins, and azoles are used as commercial antifungal agents to treat candidiasis. However, the presence of intrinsic and developed resistance against azole antifungals has been extensively documented among several Candida species. The advent of original and re-emergence of classical fungal diseases have occurred as a consequence of the development of the antifungal resistance phenomenon. In this way, the development of new satisfactory therapy for fungal diseases persists as a major challenge of present-day medicine. The design of original drugs from traditional medicines provides new promises in the modern clinic. The urgent need includes the development of alternative drugs that are more efficient and tolerant than those traditional already in use. The identification of new substances with potential antifungal effect at low concentrations or in combination is also a possibility. The present review briefly examines the infections caused by Candida species and focuses on the mechanisms of action associated with the traditional agents used to treat those infections, as well as the current understanding of the molecular basis of resistance development in these fungal species. In addition, this review describes some of the promising alternative molecules and/or substances that could be used as anticandidal agents, their mechanisms of action, and their use in combination with traditional drugs.